Arsenic and old books eaudiobook - James, Miranda (Cat in the Stacks Mystery, 2015)
Lucinda Beckwith Long, the mayor of Athena, has donated a set of Civil War–era diaries to the archives of Athena College. The mayor would like Charlie to preserve and to substantiate them as a part of the Long family legacy—something that could benefit her son, Beck, as he prepares to campaign for the state senate. Beck's biggest rival is Jasper Singletary, and their families have been bitter enemies since the Civil War. He'd like to get a look at the diaries in an attempt to expose the Long family's past sins. Meanwhile, a history professor at the college is also determined to get her hands on the books in a last-ditch bid for tenure. Now Charlie is left with a catalog of questions. The diaries seem worth killing for, and one thing is certain: Charlie will need to be careful, because the more he reads, the closer he could be coming to his final chapter . . .